SAT0152 High Cardiovascular Risk in Patients with Rheumatoid Arthritis: is Screening Effective?. (10th June 2014) - Van Den Oever, I.; Peters, M.; Lems, W.; Voskuyl, A.; van Schaardenburg, D.; Smulders, Y.; Boers, M.; Nurmohamed, M.
Abstract : Background: Since 2011, RA is regarded as an independent risk factor for cardiovascular disease (CVD) in the Dutch cardiovascular risk management (CV-RM) guidelines*. Objectives: To investigate the effect of cardiovascular risk screening on the 10-years CV risk and prescribed preventive CV risk treatment of RA patients. Methods: Consecutive RA patients visiting the outpatient rheumatology clinic of Reade, Amsterdam were included in this CV-RM study. The CV risk screening was performed by a rheumatology nurse and included assessment of the blood pressure, cholesterol levels, the disease activity score of 28 joints (DAS28) and a lifestyle questionnaire. Ten-year CV risk percentages of <10%, 10-20% and ≥20% were classified as low, intermediate and high CV risk, respectively. Patients with a history of CVD or diabetes mellitus (DM) were considered to be at high risk. The results with additional lifestyle advice were communicated to the patient and sent in a letter to the general practitioner (GP). The decision to start preventive medication was left to the GP. CV risk screening was repeated after one year and the 10-year CV risk at follow up was calculated using age at baseline. Results: In total, 94 RA patients (80% female) were screened at baseline and after one year. At baseline, the mean age was 59 years, mean DAS28 2.86 and 14 patients had CVD, DM or both. Of 76 patients, mean 10-year CV risk increased significantly from 19, 7±11, 8 to 21, 7±13, 1, p=0.007 (table 1). Four patients had a CV event. Except for systolic blood pressure none of the other CV risk factors showed significant changes after 1 year. CV risk decreased in 21 patients (28%), but increased in 42 patients (55%) (figure 1 ). At baseline, 55 patients had an indication for statin and 25 for antihypertensive therapy of which 14 used statins and 15 antihypertensives respectively, without reaching treatment goals. After one year 8 had started using statins and 17 had no statin indication anymore and although only 1 patient had started using antihypertensives, 7 patients didn't have an indication for antihypertensive therapy anymore. Of the patients who had no indication for preventive medication at baseline, 26 patients developed an indication for statin- and/or antihypertensive therapy at follow up. Ten out of 16 patients who started using preventive medication after baseline showed a decrease in 10 year CV risk. Conclusions: Overall, the 10-year cardiovascular risk showed an increase instead of the intended decrease. However, in most patients in whom preventive medication was started, the 10-years CV-risk improved. Of note is that in a substantial number of patients who had an indication for preventive medication at baseline, this was actually not initiated. Future research should therefore investigate how CV-RM can be more effectively implemented in RA patients. References: The Dutch College of General Practitioners, Multidisciplinary guidelines for cardiovascular risk management, revision 2011. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5440